COVID-19 Shocks and Emerging Market Resilience: The Pakistan Stock Market Anomaly and Policy Anticipation - Tabasam, Aftab Hussain; Mehmood, Kamran; Yunus, Fuwad (ACADEMIA International Journal for Social Sciences, 2025)
This study discovers a striking anomaly in Pakistan’s stock market during the COVID-19 crisis: rising confirmed cases drove positive daily returns, surging death rates triggered sharp declines, and accelerating recoveries supported price gains. Employing daily firm-level panel data from 200 non-financial PSX-listed companies (2020–2021) and a fixed-effects estimator with Newey–West HAC standard errors, we isolate pandemic shocks from macroeconomic controls (exchange rate, KIBOR, and inflation). The findings challenge efficient market predictions and highlight behavioral drivers, policy anticipation, contrarian buying, and herding amid extreme uncertainty. The results underscore the outsized role of credible government intervention in anchoring emerging market resilience and offer timely lessons for crisis policy design.